Influence of performance level on anaerobic power and body composition in elite male judoists - Kim, J.; Cho, H. -C.; Jung, H. S.; Yoon, J. -D. (The Journal of Strength and Conditioning Research, 2011)
This study examined the relationship between 30-second anaerobic power and body composition by performance level in elite Judoists. During a 3-month period, 10 male Korean Judo national team athletes (NT), 26 male university varsity team athletes (VT), and 28 male junior varsity team athletes (JT) were assessed for 30-second anaerobic power and body composition at the Youngin University. Anaerobic power was measured using a 30-second Wingate test. Body composition was assessed via bioelectric impedance analysis in standardized conditions using BioSpace (Korean)-specific prediction formulas. All testing occurred at the beginning of the winter nonseason period but excluded a brief weight-loss period before the competition phase. Anaerobic power measures were significantly greater (p < 0.05) in NT and VT than in JT. Fat-free mass (FFM), muscle mass (MM), and total body water in JT were also greater than in VT and JT (p < 0.05). Muscle mass in VT was significantly lower than in NT (p < 0.05). Fat-free mass in NT was strongly correlated to mean and peak anaerobic power (r = 0.77, p = 0.009; r = 0.87, p < 0.001, respectively). Varsity team athletes also indicated a moderate association between FFM and peak and mean anaerobic power (r = 0.63, p < 0.001; r = 0.48, p = 0.013, respectively). However, relationship between FFM and anaerobic power was not statistically significantly correlated in JT (r = 0.14, p = 0.470; r = 0.23, p = 0.232, separately). In conclusion, our data indicated that anaerobic power is closely correlated with increase in FFM and MM and was different dependent among performance levels. Further research in the field is warranted to elucidate the Judo-specific relationship between FFM and performance.